2007
DOI: 10.1111/j.1460-9568.2007.05422.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids mediate muscarine‐induced synaptic depression at the vertebrate neuromuscular junction

Abstract: Endocannabinoids (eCBs) inhibit neurotransmitter release throughout the central nervous system. Using the Ceratomandibularis muscle from the lizard Anolis carolinensis we asked whether eCBs play a similar role at the vertebrate neuromuscular junction. We report here that the CB 1 cannabinoid receptor is concentrated on motor terminals and that eCBs mediate the inhibition of neurotransmitter release induced by the activation of M 3 muscarinic acetylcholine (ACh) receptors. N-(piperidin-1-yl)-5-(4-iodophenyl)-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 58 publications
4
53
0
Order By: Relevance
“…Our hypothesis that MFTrPs were endowed with CB 1 receptors was supported by a GEO study (GDS1838) that showed greater CB 1 levels in skeletal muscle near the neuromuscular junction. Two new papers confirmed our results (Newman et al, 2007;Sánchez-Pastor et al, 2007), showing that CB 1 activation in motor endplates dampened acetylcholine release.…”
Section: Article In Presssupporting
confidence: 91%
“…Our hypothesis that MFTrPs were endowed with CB 1 receptors was supported by a GEO study (GDS1838) that showed greater CB 1 levels in skeletal muscle near the neuromuscular junction. Two new papers confirmed our results (Newman et al, 2007;Sánchez-Pastor et al, 2007), showing that CB 1 activation in motor endplates dampened acetylcholine release.…”
Section: Article In Presssupporting
confidence: 91%
“…There is increasing evidence that 2-arachidonylglycerol mediates the M1/M3 mAChR and group I mGluR-induced inhibition of synaptic transmission because it is abolished by phospholipase C and DAG lipase inhibitors, and by knocking out phospholipase C␤ (Melis et al, 2004;Hashimotodani et al, 2005Hashimotodani et al, , 2007Maejima et al, 2005;Newman et al, 2007;Uchigashima et al, 2007). Although we did not examine the role of phospholipase C, it was found that the carbachol-induced inhibition of evoked IPSCs was reduced by the DAG lipase inhibitor tetrahydrolipstatin to a similar extent as that produced by AM251.…”
Section: Discussionmentioning
confidence: 86%
“…Studies in the hippocampus and striatum have shown that M1/M3-induced suppression of synaptic transmission is mediated by retrograde endocannabinoid signaling. Recent evidence suggests that the endocannabinoid involved is 2-arachidonoylglycerol, which is produced via the phospholipase C/DAG lipase pathway (Melis et al, 2004;Hashimotodani et al, 2005Hashimotodani et al, , 2007Maejima et al, 2005;Newman et al, 2007;. We therefore examined whether the M1/M3-induced effects on synaptic transmission in PAG are mediated by endocannabinoids.…”
Section: Muscarinic Modulation Of Neurotransmission In Pag 1393mentioning
confidence: 99%
“…The current understanding of the pathophysiology of cramps suggests that peripheral nerve hyperexcitability and motor neuron bistability (anterior horn cell level) may play a role 14–17. The distribution of CB1 receptors in the peripheral nerves including the neuromuscular junction and spinal cord may pose an advantage of THC over medications acting solely at the peripheral nerve/neuromuscular junction (quinine sulfate) or centrally (neurontin) 18 19. Consequently, in view of the lack of randomised controlled trials, we sought to investigate the effectiveness of THC in the treatment of cramps by using a randomised, double-blind, placebo-controlled crossover design.…”
Section: Introductionmentioning
confidence: 99%